2014
DOI: 10.1016/j.ijrobp.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological Determination of Dose Escalation and Normal Tissue Toxicity in Definitive Chemoradiation Therapy for Esophageal Cancer

Abstract: PurposeThis study investigated the trade-off in tumor coverage and organ-at-risk sparing when applying dose escalation for concurrent chemoradiation therapy (CRT) of mid-esophageal cancer, using radiobiological modeling to estimate local control and normal tissue toxicity.Methods and MaterialsTwenty-one patients with mid-esophageal cancer were selected from the SCOPE1 database (International Standard Randomised Controlled Trials number 47718479), with a mean planning target volume (PTV) of 327 cm3. A boost vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…The IMRTSIB approach was based upon better radiographic findings of the biological target through PET scanning prior to CRT. This approach provides a better outline of the biological tumor within a mass, and allows RT dose intensity increase by 10% to the biological activity of tumor, without increasing the overall treatment time and the dose to the surrounding organs at risk [16] . In the Cross study, although the improvement in overall survival is 14%, the improvement for adenocar cinoma is limited [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The IMRTSIB approach was based upon better radiographic findings of the biological target through PET scanning prior to CRT. This approach provides a better outline of the biological tumor within a mass, and allows RT dose intensity increase by 10% to the biological activity of tumor, without increasing the overall treatment time and the dose to the surrounding organs at risk [16] . In the Cross study, although the improvement in overall survival is 14%, the improvement for adenocar cinoma is limited [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, radiobiological studies on esophageal cancer show that SIB treatments with RapidArc leads to better results compared to a standard dose plan. Using the RapidArc technique, acceptable dose escalation was clinically achievable for most of patients with more than 18% gain in TCP and a slight acceptable increase in NTCP for both the heart and lung [36].…”
Section: Application Of Tcp/ntcp For Plan Comparisonmentioning
confidence: 99%
“…Moreover, radiobiological studies on esophageal cancer show that SIB treatments with RapidArc leads to better results compared to a standard dose plan. Using the RapidArc technique, acceptable dose escalation was clinically achievable for most of patients with more than 18% gain in TCP and a slight acceptable increase in NTCP for both the heart and lung [36].The advantages and shortcomings of new dose delivery techniques such as IMRT and Helical tomotherapy (HT) have been discussed in terms of practical use and dosimetric benefits in the literature. Otherwise, biological comparisons of helical tomotherapy with IMRT could provide more information on the effectiveness of these treatment techniques.…”
mentioning
confidence: 99%
“…Recently, an increasing number of studies have demonstrated its feasibility, efficacy, and safety for the treatment of EC patients with the combination of IMRT and dose escalation techniques 1113. However, to the best of our knowledge, only several studies investigated the potential benefits of dose-escalated IMRT (DE-IMRT) to offer a dose escalation to the primary tumor, and improve the sparing of normal tissues compared with non-escalated IMRT (NE-IMRT) for EC patients 1416. Unfortunately, the studies failed to provide further information on esophageal toxicity, which is a common radiation-induced side effect in the treatment of EC patients 11,12,17,18…”
Section: Introductionmentioning
confidence: 99%